The Comprehensive Agreement on Respect for Human Rights and International Humanitarian Law: Perspectives from the Philippine Government, the National Democratic Front of the Philippines and Human Rights Organizations - Covero Jr, R M (KnE Social Sciences, 2018)
The study is an explication of the Comprehensive Agreement on Respect for Human Rights and International Humanitarian Law (CARHRIHL), the first of the four-item substantive agenda in the peace negotiations between the Philippine Government (GRP) and the Marxist armed movement represented by the National Democratic Front of the Philippines (NDFP). Signed in 1998, the CARHRIHL was a product of the peace process that aims to end the decades-long armed conflict via negotiated political settlement. The research objective is to provide an evaluation of the importance of the CARHRIHL in the entire peace process, and in the protection of the human rights of civilians amidst the armed conflict, while providing recommendations to strengthen the CARHRIHL’s implementing mechanism. The study identified the three main factors causing the violations in the CARHRIHL – (1) the Parties’ differences in the framework and operationalization of the CARHRIHL; (2) the not fully functioning Joint Monitoring Committee ( JMC); and (3) the militarist counter-insurgency campaigns by the GRP security forces. These have undermined the peace initiatives of various stakeholders and the future of the peace process. Among the research work’s recommendations were the following: 1. Effect procedures that protect human rights and repeal those that violate it and rehabilitate the victims. 2. The GRP and the NDFP should honor the previously signed agreements that laid down the objectives and guiding principles for the conduct of the peace talks. 3. The GRP and the NDFP must implement mechanisms of public consultations with human rights organizations concerning human rights and the peace talks. Keywords: human rights, international humanitarian law, peace process, negotiated political settlement, counter-insurgency campaigns